1998 IEEE International Joint Conference on Neural Networks Proceedings. IEEE World Congress on Computational Intelligence (Cat
DOI: 10.1109/ijcnn.1998.682276
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy prediction using connectionist and symbolic learning algorithms

Abstract: This article describes the use of connectionist and symbolic learning algorithms in the problem of Bankruptcy Prediction. Data about Brazilian banks represented by 26 or I O indicators of their current financial situation were used. The difference among the number of existent examples in the classes of bankrupt and non-bankrupt banks was livened up through the reduction of learning examples of the class of nonbankrupts and the addition of noise samples in the class of bankrupts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Since these early works there has been a large number of works based on machine-learning techniques [15,17,20]. The most successful have been based on decision trees [11,14,16,23] and neural networks [3,6,10,18,22]. Typically, all these works use different datasets and different sets of features, depending on the dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Since these early works there has been a large number of works based on machine-learning techniques [15,17,20]. The most successful have been based on decision trees [11,14,16,23] and neural networks [3,6,10,18,22]. Typically, all these works use different datasets and different sets of features, depending on the dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Fernández and Olmeda (1995) also empirically tested combining some of these techniques, with promising results. In contrast to these studies, Martinelli et al (1999) found that See4.5 outperformed ANNs. Furthermore, Laitinen and Kankaanpää (1999) showed that RPA 544 A.…”
Section: Frydman Et Al's Rpamentioning
confidence: 99%
“…Martinelli et al [29] compared between two decision tree algorithms, C4.5 and CN2, and NN on a database of Brazilian firms. C4.5 outperform the other methods.…”
Section: B Neural-network (Nn) Approachesmentioning
confidence: 99%